2020
DOI: 10.1002/jmri.27395
|View full text |Cite
|
Sign up to set email alerts
|

Signal Intensity and Volume of Pituitary and Thyroid Glands in Preterm and Term Infants

Abstract: Background Hypothalamic–pituitary–thyroid (HPT) maturation has not been extensively evaluated using neonatal MRI, even though both structures are visualized on MRI. Hypothesis That signal intensity and volume of pituitary and thyroid (T) glands on MRI in neonates may be interrelated. Study Type Retrospective. Subjects In all, 102 participants. Field Strength/Sequence 3.0T, T1‐weighted pointwise encoding time reduction with radial acquisition (PETRA). Assessment The volume of interest of the anterior pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The model can explore changes during gestation. Interestingly, the finding of coordinated P and T volumes changes (Otani et al , 2021 ) sets constraints on which parameter group might change during gestation ( Appendix Supplementary Text ).…”
Section: Discussionmentioning
confidence: 99%
“…The model can explore changes during gestation. Interestingly, the finding of coordinated P and T volumes changes (Otani et al , 2021 ) sets constraints on which parameter group might change during gestation ( Appendix Supplementary Text ).…”
Section: Discussionmentioning
confidence: 99%
“…However, qDWI revealed restricted diffusion comparable to cDWI. With the exception of TOF-MRA, quiet sequences have been reported for SWI, T2WI, FLAIR, and T1WI using fast low-angle shot or pointwise encoding time reduction with radial acquisition, 25,[31][32][33][34][35][36][37] some of which we have included in our imaging protocol for pediatric patients with MMD. TOF-MRA is usually performed preferentially to detect progressive steno-occlusion of intracranial vessels and the development of collateral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study reported that the signal intensity of the infant thyroid and anterior pituitary on 3D GRE T1WI correlated positively with the gestational age at birth and negatively with the postnatal age at examination. 7 However, the extent of the influence of gestational age at birth and postnatal age at examination on the signal intensities of the infant thyroid and anterior pituitary on T1WI is not known.…”
mentioning
confidence: 99%